Fingerprint Recognition and Verification using Fourier Domain Filtering and Histogram Equalization Techniques - G. Nancharaiah; G. Sai Teja Kumari; K. Lakshmi; J. Harika; B. Srinu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Fingerprint Recognition is a vital method in biometric identification and verification of human beings in various domains like Security, Digital Forensics, Internet of Things (IoT), and many more. Each individual human is having distinct fingerprint pattern than others, hence it is one of the most prominent and widely used method to distinguish individuals. Many research studies and solutions have been developed in biometric domain since a decade, which influences now in making the process of fingerprint recognition more optimized, faster and efficient. However, present fingerprint acquisition/recognition systems have some limitations, mainly longer computation time for fingerprint matching and evaluating the results. This paper presents a procedure for fingerprint matching that takes into account minutiae features in finger print images and the process of creating an OpenCV structure for minutiae extraction and matching of fingerprints.